THE NEURO-BEHAVIOUR OF THE NEWBORN-TO EVALUATE AND POTENTIATE. PARALLEL SESSIONS: WORKSHOPS. WORKSHOP 6 - Apóstolo, Jorge Manuel Amado (2013)
To assess the neonate neurobehavioral is very important in order to have a real profile of him. The clinical use of CLNBAS / NBO makes it possible, and, based on a structured interaction, enables practitioners to describe and interpret the behavior of the newborn. With it, and according to Gomes Pedro (2003), we can look at the forces and put special emphasis on skills. It's plausible to find difficulties and vulnerabilities but read as opportunities and development challenges. The parental support, the respect for cultural differences, the discovery of the individuality of each child, and the parent's partnership are key points to develop this touchpoint. The newborn period is a major biobehavioral development phase. The progress of self regulation of autonomic system, physiological and motor, the stabilization of newborn's states of awareness could be energized if the parents figure out appropriately all suggestions of the baby. When infants have difficulties to manage the habituation, environmental hold and handling responses are very important, because the habituation is essential in order to preserve the CNS. When some problems about regulatory systems are identified, particularly if the baby seems unable of self comfort, staying in stage VI, the emotional attunement leads parents to act. In general there's a predisposition for caregivers, especially the mother, to hurry the heteroregulation, consoling instantly, touching, breastfeeding. However the baby should be able to comfort himself and self manage the stress, but he needs time. Active interventions are required only if the situation is prolonged. But what to do with babies who respond actively and positively to the environment? What kind of assessment if he reacts satisfactory? We recall that the touchpoints model formulates a paradigm where the focus is more on strength and less on vulnerabilities. Therefore, when these babies respond well, especially if the interaction is gratifying to the couple, mother-baby, they require the continuance of positive stimuli, taking advantage of alert state, in order to reach his full potential. In this approach, neurobehavioral assessment is a toll tool that enhances the development, even when babies express a lot of competencies. The stimulus is vital for babies, competent or not. All of them are different and unique; consequently these characteristics should be discussed with parents, promoting their sense of control and competence in caring, and thus enhancing the development of the newborn. So, we need how to assess a newborn, what kind of findings we can put in evidence, and the role of parents. The importance of this model is founded in a special belief that the parents are real partners.